The Impact of the First World War on Bashkir and Tatar Muslims (1914-1918) - Salavat Iskhakov (Revue des Mondes Musulmans et de la Méditerranée)
The article analyses socio-political changes in the Muslim world of Bashkirs and Tatars of the Russian Empire, especially those who served in the Russian Army any time between 1904 and 1917. The wars of those years left deep traces, reflected in Muslim political life during the Russian Revolution and subsequent Civil War. Demobilised Muslims rose in armed struggle to defend their rights to national and religious self-determination on their home soil. In the struggle for states of their own, Muslims hoped for help from the European powers, especially from Republican France, and for recognition by the Paris Peace Conference.